Answer:
m∠ABD = 88º
m∠CBD = 23º
Step-by-step explanation:
(-10x + 58) + (6x + 41) = 111
Combine like terms
-4x + 99 = 111
Subtract 99 from both sides
-4x = 12
Divide both sides by -4
x = -3
------------------------
m∠ABD = -10x + 58
m∠ABD = -10(-3) + 58
m∠ABD = = 30 + 58
m∠ABD = 88º
m∠CBD = 6x + 41
m∠CBD = 6(-3) + 41
m∠CBD = -18 + 41
m∠CBD = 23º
Answer:
a b b
is the answer
Step-by-step explanation:
mark brainliest
Answer:
2(a - 4) + 5(b + 1) = 8. The result of this equation when solving is a = - 5b/2 + 11/2.
3(a - 1) - 2(b - 2) = -11. The result of this equation when solving is a = 2b/3 - 4.
Step-by-step explanation:
Hope this helps =)
Answer:
x = 1
Step-by-step explanation: